SPIRITUAL-EMOTIONAL WRITING THERAPY PADA SUBJEK YANG MENGALAMI EPISODE DEPRESIF SEDANG DENGAN GEJALA SOMATIS - Yudi Kurniawan; Retno Kumolohadi (Universitas Ahmad Dahlan, 2015)
AbstractThis study aims to determine the effect of spiritual-emotional writing therapy toward person with moderate depressive diagnosis. This study involved 20-year-old student with a moderate depressive episode as a subject. Precipitating of her disorder is the events of pramarriage pregnancy in 2012. Data were collected by interview and observation method Quantitative scale. Depression scores were measured using a scale of HDRS (Hamilton Depressive Rating Scale) and obtained a score of 20 (Depressive were heading severe). Intervention is provided by Spiritual Writing Therapy which is a modificationof the technique Cognitive Behavior. Islamic spiritual element attached in the form of reflection of gratitude (adaptation emotional) of all the painful events experienced by the subject. Data were analyzed by comparing the state of mind and behavior of the subject between the situation before and after the intervention. The results showed that therapeutic writing attached with cognitive behavioral approach is able to reconstruct the thinking and behavior of the subject, so as to be positive in looking at ourselves and the world around.Keywords:gratitude, moderate depressive disorder, spiritual-emotional writing therapy